Employee Adaptation Patterns in Utilizing Digital Fundraising Channels during the Covid-19 Pandemic - Qomar, Moh. Nurul; Fitriyati, Arsyada; Khadziqa, Innaki; Hidayatunni’mah, Syafa (Munazzama: Journal of Islamic Management and Pilgrimage, 2022)
This research was conducted to examine employees’ adaptation patterns using digital fundraising channels at LAZ IZI Central Java. The research type used in this study was qualitative, using a phenomenological approach. The primary data was obtained from observations and interviews with LAZ IZI Central Java employees, and the secondary data were taken from books, articles, and journals. This study found that the adaptation pattern of LAZ IZI Central Java employees in the New Normal period did not experience any significant obstacles because digital fundraising had become part of their activities before the COVID-19 pandemic. However, digital fundraising competence was still improved through training and workshops carried out internally and externally.